Portal Venous Circulating Tumor Cells Undergoing Epithelial-Mesenchymal Transition Exhibit Distinct Clinical Significance in Pancreatic Ductal Adenocarcinoma - Pan, Yujin; Li, Deyu; Yang, Jiuhui; Wang, Ning; Xiao, Erwei; Tao, Lianyuan; Ding, Xiangming; Sun, Peichun; Li, Dongxiao (Frontiers in Oncology, 2021)
Background: Much importance is attached to the clinical application value of circulating tumor cells (CTCs), meanwhile tumor-proximal CTCs detection has interested researchers for the unique advantage. This research mainly discusses the correlation of portal venous (PoV) CTCs counts in different epithelial-mesenchymal transformation status with clinicopathologic parameters and postoperative local recurrence or distant metastasis in pancreatic ductal adenocarcinoma patients (PDAC). Methods: PDAC patients (n=60) who received radical resection were enrolled in this research. PoV sample from total patients and peripheral blood (PV) blood from 32 patients were collected to verify spatial heterogeneity of CTCs distribution, then exploring the correlation with clinicopathologic parameters and clinical prognosis. Results: CTCs detectable rate and each phenotype count in PoV were higher than those of the PV. Patients with recurrence had higher PV and PoV epithelial CTCs counts than recurrence-free patients (P<0.05). Some unfavorable clinicopathologic parameters were closely related to higher PoV CTCs count. Multivariate factor analysis demonstrated that PoV mesenchymal CTCs ≥1 /5 ml was independent risk factors for metastasis free survival (MFS) (P=0.005) and overall survival (OS) (P=0.043). Conclusions: Our research demonstrated that portal vein is a preferable vessel for CTC phenotype detection for PDAC prognosis assessment and patients with PoV M-CTC ≥ 1 /5 ml had shorter MFS and OS. PoV CTC phenotype detection has the potential to be a reliable and accurate method to identify patient with high risk of metastasis for better stratified management of PDAC patients.